2012
DOI: 10.1159/000342928
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the P2X<sub>7</sub> Purinergic Receptor and c-Jun N-Terminal and Extracellular Signal-Regulated Kinases in Cyclooxygenase-2 and Prostaglandin E<sub>2</sub> Induction by LL-37

Abstract: Periodontal disease is caused by microorganisms and host-derived inflammation involving increased cyclooxygenase-2 (COX-2) expression and prostaglandin E2 (PGE2) production. We previously demonstrated that human β-defensin-3 induces COX-2 and PGE2 in human gingival fibroblasts (HGFs). We, therefore, aimed to examine the inducible effects of LL-37, the only cathelicidin expressed in humans, on COX-2 expression and PGE2 synthesis in HGFs and to elucidate the relevant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 72 publications
3
24
1
1
Order By: Relevance
“…It is interesting to note that there are other endogenous P2X7 receptor ligands, such as cationic antimicrobial peptide LL-37 (43,44). LL-37 is a cathelicidin-type peptide that destabilizes the surface of the pathogen membrane.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that there are other endogenous P2X7 receptor ligands, such as cationic antimicrobial peptide LL-37 (43,44). LL-37 is a cathelicidin-type peptide that destabilizes the surface of the pathogen membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study also showed that LL-37 promotes LTB 4 and TXA 2 production via P2X 7 R (8). P2X 7 R is a ligand-gated ion channel, which is highly expressed by cells of the hematopoietic lineage, and it mediates cell death, killing of infectious organisms, and regulation of inflammatory responses (9). This receptor exists within the plasma membrane as a large multimolecular complex, consisting of b-actin, integrin b2, three heat shock proteins (10), and nonmuscle myosin (11).…”
mentioning
confidence: 99%
“…Interestingly, LL-37 has been shown by other groups to activate P2X7R directly in a manner not affected by apyrase (23, 39, 40). The differences in our results to those previously reported may stem from the different methodologies used in each study.…”
Section: Discussionmentioning
confidence: 91%